1925
DOI: 10.1007/bf01740353
|View full text |Cite
|
Sign up to set email alerts
|

Beitrag zur Frage der Inkret-(Hormon)-Wirkung des Cholins auf die motorischen Funktionen des Verdauungskanales

Abstract: Unsere Versuche schliel~en an diejenigen yon Le Heux 1) an. Er hat bekanntlich der allgemeineren Beobachtung, wonach die Bewegung insbesondere des S~ugetierdiinndarmes nicht nut yon bestimmten Nerven aus beeinflul~t wird, sondern Stoffe vorhanden sind, die sie regeln, eine bestimmtere Fassung gegeben und an Hand yon Versuchen den Schlul3 gezogen, dal~ Cholin ein solches Produkt darstellt. Der iiberlebende Darm gibt Cholin ab. Nun ist bekannt, dal~ diese Verbindung und insbesondere ihre Derivate (z. B. Acetylch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1929
1929
1954
1954

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is not lactylcholine, as this has too low an RF value and has a very low biological activity. We have not had any amino-acid esters available for comparison, but those described in the literature, glycylcholine (Abderhalden et al 1925), alanyl-and leucylcholine (Freudenberg & Keller, 1938) have been reported to have very feeble physiological activity. There is some evidence that F is a keto-acid ester, in that F and its alkaline hydrolysate reacted with 2: 4-dinitrophenylhydrazine and 4-nitrophenylhydrazine to give substances with absorption spectra in the visible and near ultra-violet, but the presence of pyruvate, acetoacetate, a-ketoglutarate or oxaloacetate could not be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…It is not lactylcholine, as this has too low an RF value and has a very low biological activity. We have not had any amino-acid esters available for comparison, but those described in the literature, glycylcholine (Abderhalden et al 1925), alanyl-and leucylcholine (Freudenberg & Keller, 1938) have been reported to have very feeble physiological activity. There is some evidence that F is a keto-acid ester, in that F and its alkaline hydrolysate reacted with 2: 4-dinitrophenylhydrazine and 4-nitrophenylhydrazine to give substances with absorption spectra in the visible and near ultra-violet, but the presence of pyruvate, acetoacetate, a-ketoglutarate or oxaloacetate could not be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…We have already referred to enteramin, but the wall of the digestive tract contains, in addition, choline and acetylcholine which have been extracted from the m. externa and from the mucosa. According to Abderhalden & Paffrath (1925) the mucosa is the main source for the choline of the intestinal wall. No systematic survey has been made of the distribution of acetylcholine in the different layers of the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%